Insecticidal efficacy of beauveria bassiana, diatomaceous earth and fenitrothion against rhyzopertha dominica and tribolium castaneum on stored wheat - Dal Bello, Gustavo (2018)
Bioassays were conducted in stored grains to evaluate the combined use of the entomopathogenic fungus Beauveria bassiana, diatomaceous earth (DE) and fenitrothion against adults of Rhyzopertha dominica and Tribolium castaneum. The insecticide agents were applied to wheat as follows: the fungus at 1 × 108 conidia/kg of wheat, DE at 3 g/kg of wheat and fenitrothion at a rate of 0.15 ml/kg of wheat (25% of field dose rate). Surviving insects and progeny production were monitored at thirty-day intervals until four months. For both insect species, significantly less progeny was produced on wheat treated with fenitrothion and DE + B. bassiana formulations in comparison with controls. The effect of insecticides on the grain damage, germination power of wheat and bulk density was also evaluated. After four months, B. bassiana mixed with DE reduced the damaged insect grains by 50% in comparison with both fenitrothion and control treatments. Trials using DE caused a reduction in bulk density while there were no significant differences for germination testing between treatments.